European Views on Elmolo Ethnic Group (Kenia, 1887-1975) : The Normalization of Vanishing Africa - Martínez Sánchez, Ismael; Nevado Hernández, Ignacio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This article examines thirteen journeys undertaken between 1887 and 1973 to Kenya by explorers, anthropologists, and artists, in order to assess the image they conveyed of the Elmolo People through their writings, illustrations, and photographs. It reveals how each expedition inherited a distorted view, shaped by ideas such as poverty, risk of extinction, fishing, silence, shyness, hospitality, ritual hippo hunting, and interethnic relations. Colonial stereotypes — notably the notion of a Vanishing Africa — became normalised. The article offers a new perspective by incorporating the photographic gaze, whose static and often stereotyped depictions contrast with the supposed progress of textual knowledge.